DNA Damage in Predatory Insects Comet Assay and Different Bioassay for Insecticides in Insects - Hafza Irshad, Saad Irfan, Asia Noureen, Arshad Ali, Inamullah, Farhad Badshah, Muhammad Babar Malook, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: This study aims to quantify DNA damage in predatory insects by the use of a comet assay or a bioassay designed for insecticides, and to identify the primary parameters that influence the efficacy of a bioassay or a comet test. Methods: The present study involved the implementation of a qualitative analysis of the comet assay as a methodological approach. A group of scientists has studied DNA damage in predatory insects. Their research focused on understanding the impact of environmental factors on the DNA of these insects. Results: By analyzing the DNA damage, they were able to identify potential threats to their survival and develop strategies for their conservation. The comet assay has revealed both the overall extent of damage in cells of predatory insects and the severity of damage incurred by individual cells. The comet assay is a field that can and should expand and diversify. Practical Implications: Recent advances in the area include high throughput variants of the method, investigations into epigenetics via methylation, chromosome-separated comets, and the isolation of individual genes from inside the comet. Conclusion: The problem at hand is and has been the laborious process of rating comets. The field of cometology is on the verge of adopting a fully automated photo analysis system, but first they need one. Meanwhile, once every two years, researchers from all around the world gather to share their latest findings and debate the latest developments in their field at the International Comet Assay Workshop. Keywords: Bioassay, Cometassay, DNA, Insects